2021
DOI: 10.1177/14648849211044559
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of constructive and solutions journalism research

Abstract: Academic activity surrounding constructive and solutions journalism has surged in recent years; thus, it is important to pause and reflect on this growing body of work in order to understand where the field can and should go in the future. We conducted a systematic review of existing literature on solutions and constructive journalism ( N = 94), in an effort to (1) describe the state of this field by identifying the patterns and trends in the methodological and conceptual approaches, topics, institutions, coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 34 publications
1
11
0
2
Order By: Relevance
“…Research on constructive journalism also seems to be lacking in Indonesia. This aligns with Lough & McIntyre's (2021) research findings that mainly found constructive journalism research in the United States and Europe-lacking research in Asia, Africa, and Latin America. They call for more research globally to compare how constructive journalism is applied in different countries.…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…Research on constructive journalism also seems to be lacking in Indonesia. This aligns with Lough & McIntyre's (2021) research findings that mainly found constructive journalism research in the United States and Europe-lacking research in Asia, Africa, and Latin America. They call for more research globally to compare how constructive journalism is applied in different countries.…”
Section: Introductionsupporting
confidence: 89%
“…The term "constructive journalism" was coined by Karen McIntyre and Cathrine Gyldensted in 2017. As of December 2020, 73 published peer-reviewed articles and 21 thesis or dissertations on the concept are found (Lough & McIntyre, 2021). Constructive journalism aims for a more balanced approach where journalists address problems and the solutions and positive examples of how to handle challenges (Skovsgaard & Andersen, n.d.).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dentro de la categoría de las especializaciones periodísticas, en la que se enmarca el objeto de estudio de la presente investigación, se han abordado revisiones sistemáticas sobre el periodismo narrativo (Van Krieken; Sanders, 2021), el periodismo constructivo y de soluciones (Lough;McIntyre, 2021), el periodismo ambiental (Balbé; Loose, 2020) y el periodismo científico (González-Pedraz;Campos-Domínguez, 2015).…”
Section: Meta Investigación Sobre Periodismo Y Periodismo De Investig...unclassified
“…While still relatively new to scholarly study, a healthy body of research has been published about solutions and/or constructive journalism (Lough & McIntyre, 2023). Several of these studies tested the effects of these practices on the audience using experimental methods (e.g., Dahmen et al, 2021;Meier, 2018) and mirrored the claims made from the non-profit organizations that support the practices (Green, n.d.;Green-Barber, 2018).…”
mentioning
confidence: 99%